2003
DOI: 10.1002/clc.4960260411
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of heart rate variability for the recurrence of chronic atrial fibrillation after electrical cardioversion

Abstract: SummaryBackground: The relation between heart rate variability (HRV) and occurrence of atrial fibrillation (AF) in paroxysmal AF has been well studied, but there are controversial observations regarding the relation of HRV parameters to the recurrence of chronic AF after cardioversion.Hypothesis: The present study compared HRV parameters of patients with chronic AF on the second day of cardioversion with a healthy control group and investigated their predictive value for AF recurrence.Methods: Forty-one patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Although a relationship between HRV parameters and atrial electrophysiological properties has been proposed by many clinical studies [4,5,[11][12][13][14], it remains to be established to what extent the HRV of the sinus node correlates to changes in atrial autonomic tone.…”
Section: Study Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a relationship between HRV parameters and atrial electrophysiological properties has been proposed by many clinical studies [4,5,[11][12][13][14], it remains to be established to what extent the HRV of the sinus node correlates to changes in atrial autonomic tone.…”
Section: Study Limitationsmentioning
confidence: 99%
“…A comparison of our results in terms of predictive value of HRV analysis with results of previous studies is quite impossible. In fact, the HRV analyses were often obtained during a 24-h ECG Holter recording performed in the first [11][12][13] or in the second 24 h [14] after AF interruption. Moreover, the results of HRV analysis were used to predict late AF recurrence [11][12][13][14].…”
Section: Previous Studiesmentioning
confidence: 99%
“…Changes in autonomic balance seem to play a role in the pathogenesis of arrhythmias following electrical CV and might have a predictive value 1 . The suppression of parasympathetic activity is associated with ERAF after CV 5,9 . Although previous studies have shown that cardiac autonomic activity is modified by electrical CV and predicts the relapse of AF, it seems unlikely that the waveform applied has an effect on late recurrences of AF 10,11 .…”
Section: Discussionmentioning
confidence: 99%
“…1 The suppression of parasympathetic activity is associated with ERAF after CV. 5,9 Although previous studies have shown that cardiac autonomic activity is modified by electrical CV and predicts the relapse of AF, it seems unlikely that the waveform applied has an effect on late recurrences of AF. 10,11 According to our results, HRV is markedly depressed after Mo CV as opposed to Bi CV.…”
Section: Discussionmentioning
confidence: 99%
“…1 With regard to treatment, the heart rate control strategy is as effective as the rhythm control strategy, 2,3 but the target heart rate in this strategy is as yet unclear, although the heart rate during AF may be related to the prognosis and/or the quality of the patient's life. A heart rate less than 90 beats/min at rest and 115 beats/min during moderate exercise has been recommended, 4 but is based on clinical experience.…”
mentioning
confidence: 99%